Simulação de Cenários para Regulação Emocional de Investidores em Ações - Bortoli, Alcinéia De (2022)
Most investors enter the stock market with little knowledge of the subject and learn as they trade stocks. The learning process can present losses and gains depending on the investor's profile and risk exposure. Many investors make wrong decisions, whether beginners or experienced investors because human rationality for decision-making is limited (Simon, 1981). Moreover, both emotions and cognitive biases interfere in this decision-making process. This research aimed to construct a script based on Rojo's Scenario Simulation Model for the emotional regulation of stock investors. The exploratory-descriptive method was used, the approach was qualitative, and the data collection technique was done through the snowball technique. The sampling method adopted was non-probability by convenience. The mapping of emotions, the use of emotion regulation techniques (Gross 2008), the mapping of heuristics and biases (Kahneman 2012), as well as scenario simulation (Rojo 2006) can contribute to bold decisions when buying and selling stocks, even for the most experienced investors. The results of this research reinforce the importance of paying attention to the presence and use of heuristics and biases when making decisions and the potential consequences, not always pleasant, arising from them.